ADAPTASI IDENTITAS ANAK PELAKU WAYANG BOCAH DI LINGKUNGAN SEKOLAH MODERN - Suparti; Widodo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This qualitative case study explores the identity adaptation and psychological impacts on children performing in Wayang Bocah within a modern school ecosystem. Integrating Social Identity Theory and Social Construction Theory, this study examines children's dynamics across two contradictory domains: traditional art studios and public schools. Data were gathered through in-depth interviews, participant observation, and documentary analysis involving child actors, parents, and teachers. The results reveal a phenomenon of "identity compartmentalization," where children develop dual adaptation strategies to secure peer acceptance without losing their cultural ties. The clash of values between tradition and modernity does not trigger an identity crisis, but rather fosters high role flexibility and social resilience in children. This interdisciplinary study contributes significantly to developmental psychology and cultural sociology in understanding how contemporary children navigate traditional spaces in the digital era.